CONTAMINATION SALMONELLA SPP. IN BROILER CHICKEN MEAT SOLD IN THE BADUNG MARKET DURING THE TRANSITIONAL SEASON PERIOD - Nabila Dwifitria Azis; Hapsari Mahatmi; I Wayan Suardana; Gede Putra Sanjaya (Buletin Veteriner Udayana, 2024)
The presence of Salmonella spp. in animal food products is highly undesirable and strictly regulated in Indonesian law. One of the factors that causes contamination is the climate and conditions of the place of sale. This study aims to determine the presence of Salmonella spp. bacteria in broiler meat that sold at Badung Market during the transitional season period. The research sample was fresh broiler chicken meat, namely 15 samples taken randomly from 15 broiler chicken traders. The isolation stage begins with enrichment using Selenite broth media, followed by isolation of bacteria using selective media, namely Salmonella Shigella Agar (SSA), identification using the Gram staining method, and Biochemical Tests including the Triple Sugar Iron Agar Test, Methyl Red, Indole, and Citrate tests. The results of the research found that 5 of 15 (33,3%) samples were identified as contaminated with Salmonella spp. Based on the research results, it can be concluded that broiler chicken meat sold in the Badung market during the transitional season is of poor quality. It is hoped that the government will pay more attention and provide education regarding the procedures and procedures for selling chicken meat according to standards and implement the applicable regulations more strictly, because this can have a serious impact on public health.